Sustainable development goals, universal health coverage and equity in health systems: the Orang Asli commons approach. (2016) - Wong, Y. S.; Allotey, P.; Reidpath, D. D.
Abstract : Universal health coverage is a key health target in the Sustainable Development Goals (SDGs) that has the means to link equitable social and economic development. As a concept firmly based on equity, it is widely accepted at international and national levels as important for populations to attain 'health for all' especially for marginalised groups. However, implementing universal coverage has been fraught with challenges and the increasing privatisation of health care provision adds to the challenge because it is being implemented in a health system that rests on a property regime that promotes inequality. This paper asks the question, 'What does an equitable health system look like?' rather than the usual 'How do you make the existing health system more equitable?' Using an ethnographic approach, the authors explored via interviews, focus group discussions and participant observation a health system that uses the commons approach such as which exists with indigenous peoples and found features that helped make the system intrinsically equitable. Based on these features, the paper proposes an alternative basis to organise universal health coverage that will better ensure equity in health systems and ultimately contribute to meeting the SDGs.